Gambling, the state and society in Thailand, c. 1800-1945 - Warren, James A. (Routledge studies in the modern history of Asia (2005), 2013)
"Charts the development of gambling in Thailand and relates it to the development of Thai state and society, showing how gambling was a fundamental issue hugely affecting political developments. It considers the difference between law and how law is enforced, outlining how the Thai elite, though professing opposition to gambling, often both tolerated and profited from it, as did the police"--Provided by publisher.